Toward an Optimal Donation Solicitation: Evidence from the Field of the Differential Influence of Donor-Related and Organization-Related Information on Donation Choice and Amount. (March 2018) - Fajardo, Tatiana M.; Townsend, Claudia; Bolander, Willy
The present research decomposes consumer donation behavior into two components: donation choice (i.e., whether to donate) and donation amount (i.e., how much to donate). It then considers how information related to the donor and information related to characteristics of the soliciting organization may differentially influence the two decisions. Results from four field experiments suggest that donor-related appeals have a greater effect on the donation choice decision (vs. organization-related appeals), whereas organization-related appeals have a greater effect on the donation amount decision (vs. donor-related appeals). This might lead one to conclude that presenting both types of appeals in a solicitation is ideal. However, the studies presented herein also suggest that this strategy may backfire. The simultaneous presentation of donor- and organization-related appeals can hamper both donation response rates and average contribution amounts. To address this issue, the authors identify and test an alternative solicitation strategy for maximizing solicitation effectiveness. This strategy involves a multistep request process that capitalizes on an understanding of the differential influence of donor- and organization-related information on donation choice and amount decisions.